A criação do Bispado das Alagoas: religião e política nos primeiros anos da República dos Estados Unidos do Brazil (1889-1910) - Nunes, Márcio Manuel Machado (2016)
The Diocese of Alagoas was created at July 2, 1900 through the Papal Bull Postremis hisce temporibus of Pope Leo XIII. It was an old dream of the Province of Alagoas, which only came true during the republican period. With the separation of Church and State in Brazil by Decreto 199-A of January 7, 1890, the Padroado had become extinct and Church had deal with this new reality without the “official” support from the Republican Government. The scope of this research is to undertake an analysis of the creation process of the Diocese of Alagoas, from its first proposal in the early nineteenth century until its consolidation, with the bishopric of Dom Antônio Brandão. One notes that the good relationship between Church and State in Alagoas was against to the prevailing situation in the Republic’s politics, which was noticeably positivist and secular. Despite presenting peculiarities at this time of separation, the case of Alagoas was not unique. One of the goals of this research is to better understand how the imbricated affinity between religion and politics occurred at Alagoas territory in the beginning of century XX. To help us comprehend the religious experience of the faithful of Alagoas and the way how the alliance between the Catholic Church and the secular State in Alagoas in the first years of the Republic in the United States of Brazil we will follow closely the formative year of Dom Antônio Brandão, the prelate responsible of the creation of the Bishopric of Alagoas.